2023
DOI: 10.3390/buildings13020536
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations and Seismic Assessment of a Historical Stone Minaret in Mostar

Abstract: Minarets, tall structures, connected or not to the mosque attract attention due to their specific architectural features. Vulnerability to seismic damage has been witnessed throughout history on tall and slender structures after earthquake ground motions. In that respect, it is of the utmost importance to investigate the dynamic characteristics and resilience of historical stone minarets. This paper aims to provide the results of an on-site dynamic investigation of a stone minaret in Mostar and deliver its sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In the meantime, the first story drift was found to be decreased because of the band type window and slope effect. Tresnjo et al [8] conducted an experimental dynamic campaign and integrated that with a seismic assessment for a historical minaret. The comparison between experimental and eigen analyses shows a good agreement in terms of dynamic characteristics.…”
Section: Seismic Impact On Buildings: a Bird's Eye Viewmentioning
confidence: 99%
“…In the meantime, the first story drift was found to be decreased because of the band type window and slope effect. Tresnjo et al [8] conducted an experimental dynamic campaign and integrated that with a seismic assessment for a historical minaret. The comparison between experimental and eigen analyses shows a good agreement in terms of dynamic characteristics.…”
Section: Seismic Impact On Buildings: a Bird's Eye Viewmentioning
confidence: 99%
“…To bridge the gap in terms of establishing the relationships between experimental investigations with simulation outcomes, a few studies were found in the literature to assess the dynamic response of traditional masonry structures. For instance, Gentile and Saisi (2007) deployed finite element analysis (FEA) to assess the ambient dynamic response of a 74 m tall bell tower built in the 16th century [20,[25][26][27][28][29][30]. By integrating material properties in conjunction with geometry, slenderness ratio, and establishing boundary conditions to solve the equations of motion, the model was simulated under ambient environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The bell tower was damaged during the Petrinja earthquake in such a way that its functionality was compromised, so an evaluation of its seismic resistance is required. Recently, the application of the results of experimental determination of modal parameters with AMT for different buildings has gained importance [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Gentile and Saisi [15] presented the results of investigations based on ambient vibrations carried out to evaluate the structural condition of a masonry bell tower built in the XVII century and about 74 m high.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters of the materials were derived by calibrating finite element models (FEM), using data collected during a study campaign carried out with an OMA application. Recently, Trešnjo et al [29] presented the results of a dynamic on-site investigation of a stone minaret in Mostar and provided a seismic evaluation. The on-site investigation included dynamic identification of the minaret through environmental vibration tests and qualitative assessment of the masonry through sound pulse velocity measurements.…”
Section: Introductionmentioning
confidence: 99%